Strategi Komunikasi Pemasaran Bilik Thrift dalam Meningkatkan Brand Image di Media Sosial Instagram - Arini Sabila Anjani; Trimanah Trimanah (INDO PUBLISHING, 2026)
This study is motivated by the increasingly intense competition in the thrift business in the digital era, which has driven businesses to optimize marketing communication strategies through social media, particularly Instagram, to build a positive and consistent brand image. Bilik Thrift is a thrift fashion business in Semarang that actively utilizes Instagram for marketing communication while facing the challenge of unofficial accounts that could damage its brand image. This study aims to determine Bilik Thrift's marketing communication strategy for enhancing its brand image on Instagram. The theories used are Social Media Marketing (SMM) by Tuten and Solomon (2018) through five strategic pillars, namely content strategy, community management, social advertising, analytics and metrics, and regulation and ethics, together with the brand image theory by Kotler and Keller (2016). This research employed a descriptive qualitative method with a constructivist paradigm. Data were collected through in-depth interviews and documentation with two internal informants, the owner and the social media administrator, selected through purposive sampling, and validated through source triangulation. The findings show that Bilik Thrift synergistically implements the five SMM pillars